The relationship of plasma miR-503 and coronary collateral circulation in patients with coronary artery disease - Fei, Yu; Hou, Jianhua; Xuan, Wei; Zhang, Chenghua; Meng, Xiuping (Life sciences (1973), 2018)
Although angiogenesis plays an important role in coronary collateral circulation (CCC) formation and there are many determinants of coronary angiogenesis, they cannot fully explain the mechanism of CCC formation or as potent biomarker for CCC status. Therefore, there is of great clinical significance to identify the novel molecules associated with CCC. Previously, miR-503 exerts anti-angiogenesis effect via inhibition of VEGF-A and its expression is associated with many angiogenesis-related factors. Thus, we aimed to investigate the relationship of plasma miR-503 with CCC formation as well as its predictive power for CCC status in patients with coronary artery disease. Among patients who underwent coronary angiography with coronary artery disease and a stenosis of ≥90% were included in our study. Collateral degree was graded according to Rentrop Cohen classification. The patients were divided to good CCC group (grade 2 or 3) and poor CCC group (grade 0 or 1) according to Rentrop grade. We investigated the plasma levels of miR-503 and VEGF-A by ELISA or q RT-PCR, respectively. In addition, we assayed the correlations of plasma miR-503 with VEGF-A or Rentrop grade using the spearman correlation test and its predictive power by receiver operating characteristic (ROC) and binary logistical regression analysis. Our data showed that plasma VEGF-A was significantly higher in good CCC group than that in poor group. Plasma miR-503 was lower in CAD patients with good CCC or poor CCC compared with control subjects and lowest in good CCC group. In addition, miR-503 negatively correlated with VEGF-A and Rentrop grade, respectively. Moreover, miR-503 displayed more potent predictive power for CCC status than VEGF-A, but its sensitivity and specificity for CCC status were only 72.4 or 60.9%, respectively. Lower plasma miR-503 level was related to better CCC formation, accompanied by up-regulation of VEGF-A. In addition, miR-503 displayed potent predictive power for CCC status, but its sensitivity and specificity were not high enough, indicating that miR-503 might be as an additional prognosis biomarker for CCC.